التوجه إلى بناء المدن الذكية كإستراتيجية لتحقيق التنمية المستدامة - شنوف، جمال; مراحي ،مختار (جامعة الوادي University of Eloued, 2025)
هدفت هذه الدراسة إلى البحث في موضوع المدن الذكية التي أصبحت التوجه الجديد لجل دول العالم من أجل تحسين جودة حياة الأفراد وتحقيق التنمية المستدامة، حيث تم اعتماد المنهج الوصفي بوصف متغيرات الدراسة في قالبهما النظري، مع الأخذ بعين الإعتبار التجربة الرائدة التي قامت بها دبي في إقامة المدينة الذكية كنموذج يحتذى به في هذا المجال. توصلت الدراسة إلى أن دبي قطعت شوطا رهيبا في مجال التحول إلى المدن الذكية والتي ساهمت بشكل كبير في تحقيق التنمية المستدامة، فرغم كل التحديات والمعوقات التي واجهتها، إلا أنها تبقى متيقنة بتحقيق تنميتها المستدامة وضمان رفاهية الأفراد والأجيال المستقبلية، حيث نجحت في بناء عدة مدن مستدامة أهمها مدينة دبي المستدامة، مدينة دبي الجنوب، مدينة دبي للسيليكون، بالاعتماد على مجموعة من الآليات والتطبيقات والأنظمة التي ساهمت في نجاحها، كما أصدرت مجموعة من القوانين والمشروعات التي تعزز حفظ السلامة والاستدامة البيئية مع تخفيض الطلب على الطاقة. This study aimed to explore the topic of smart cities, which have become a new trend in most countries around the world, with the goal of improving the quality of life for individuals and achieving sustainable development. A descriptive approach was adopted, describing the study variables in their theoretical form, taking into account Dubai's pioneering experience in establishing a smart city, which serves as a model to be emulated in this field. The study concluded that Dubai has made great strides in the field of transformation into smart cities, which has contributed greatly to achieving sustainable development. Despite all the challenges and obstacles it has faced, it remains confident in achieving its sustainable development and ensuring the well-being of individuals and future generations, as it has succeeded in building several sustainable cities. The most important of which are Dubai Sustainable City, Dubai South City, and Dubai Silicon City, relying on a set of mechanisms, applications and systems that have contributed to their success. It has also issued a set of laws and projects that enhance safety and environmental sustainability while reducing energy demand.
Moving towards building smart cities as a strategy to achieve sustainable development - Dubai as an example –
Keywords: مدينة ذكية; بيئة; تكنولوجيا المعلومات والاتصالات; تنمية مستدامة; تنمية عمرانية مستدامة; دبي; smart city; environment; information and communications technology; sustainable development; sustainable urban development; Dubai.